2020
DOI: 10.3390/cancers12061555
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling of Retinoblastoma-Derived Exosomes Reveals Potential Biomarkers of Vitreous Seeding

Abstract: Retinoblastoma (RB) is the most common tumor of the eye in early childhood. Although recent advances in conservative treatment have greatly improved the visual outcome, local tumor control remains difficult in the presence of massive vitreous seeding. Traditional biopsy has long been considered unsafe in RB, due to the risk of extraocular spread. Thus, the identification of new biomarkers is crucial to design safer diagnostic and more effective therapeutic approaches. Exosomes, membrane-derived nanovesicles th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 127 publications
0
33
0
Order By: Relevance
“…A growing body of evidence suggests that sEVs might be useful as biomarkers in many diseases [ 102 , 104 , 105 , 106 ], as well as prognostic agents providing information about the phase of disease or predicted therapy outcomes [ 107 , 108 , 109 ]; sEVs transfer specific cargo components depending on the cell of origin, and ensure a safe environment for transported compounds. This allows their delivery to both neighboring and distant cells, which is an important modality of communication between tissues and organs.…”
Section: Resultsmentioning
confidence: 99%
“…A growing body of evidence suggests that sEVs might be useful as biomarkers in many diseases [ 102 , 104 , 105 , 106 ], as well as prognostic agents providing information about the phase of disease or predicted therapy outcomes [ 107 , 108 , 109 ]; sEVs transfer specific cargo components depending on the cell of origin, and ensure a safe environment for transported compounds. This allows their delivery to both neighboring and distant cells, which is an important modality of communication between tissues and organs.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, tumoral exosomes can induce drug resistance carrying miRNAs that target antiapoptotic and immune-suppressive pathways or ABC transporters, which export chemotherapeutic agents out of recipient cells ( Santos and Almeida, 2020 ). Given their involvement in cancer progression and their presence in different biological fluids, there have been increasing efforts toward their characterization as a source of possible diagnostic and prognostic biomarkers even in pediatric oncology ( Colletti et al, 2017 , 2019 , 2020 ; Galardi et al, 2019 , 2020 ) and as a delivery tool for biomedical applications ( Rezaie et al, 2018 ; Rahbarghazi et al, 2019 ; Jabbari et al, 2020b ; Wu Z. et al, 2020 ).…”
Section: Exosomes: Biogenesis Release and Functionsmentioning
confidence: 99%
“…Of these, 25 are upregulated, and eight are downregulated [ 112 , 113 ]. In another study by Galardi A et al, the proteomic profiling of the exosomes constituents has identified 99 proteins that are exclusively present in RB tumors [ 114 ]. We have analyzed the targets of the miRNAs from both these studies [ 112 , 113 ] from the proteins identified in RB tumor exosomes [ 114 ].…”
Section: Mirna and Their Targets In Retinoblastomamentioning
confidence: 99%
“…In another study by Galardi A et al, the proteomic profiling of the exosomes constituents has identified 99 proteins that are exclusively present in RB tumors [ 114 ]. We have analyzed the targets of the miRNAs from both these studies [ 112 , 113 ] from the proteins identified in RB tumor exosomes [ 114 ]. hsa-miR-494 (upregulated) and hsa-miR-9 (downregulated) have the maximum number of targets in proteins identified in RB tumor exosomes ( Table 1 ).…”
Section: Mirna and Their Targets In Retinoblastomamentioning
confidence: 99%
See 1 more Smart Citation